Fatalistic Beliefs and Cervical Cancer Screening Among Mexican Women. Issue 1 (2nd January 2016) - Marván, Ma. Luisa; Ehrenzweig, Yamilet; Catillo-López, Rosa Lilia
Abstract : Fatalistic beliefs about cervical cancer were studied in 464 Mexican women, and how such beliefs relate to participation in cervical cancer screening was evaluated. Rural women were less likely than urban women to have had a Pap test and more likely to believe that the illness is due to bad luck or fate. These were also the beliefs most associated with nonscreening among rural women, whereas for urban women the belief most associated with nonscreening was "there is not much I can do to prevent cervical cancer."